Comunicación intrafamiliar y la conducta agresiva de los adolescentes de la unidad educativa Caluma - Narvavez Moya, Rosali Mariela (2017)
The main objective of this research is to determine the aggressive behavior of the adolescents of the Caluma Educational Unit, due to the poor communication they have in their homes. The sample to be investigated corresponds to a total of 80 male and female students from 11 to 18 years of age, it will also work with 65 teachers and 80 parents. The methodological design used in this research is descriptive and explanatory. For data collection, a survey directed to parents was used, as well as an Agresión questionnaire (AQ) from Buss and Perry adapted in Spain by Andre, Peña and Giraña (2002) Once the analysis is done, it is deduced that family communication is important given that, access to the integration of its members is the same that favors and allows to grow, develop, mature, resolve conflicts, understand each other and in society. The results obtained in the process of data interpretation indicate that the institution shows a high rate of verbal aggression in adolescents. Product of different manifestations due to the passive and sometimes aggressive communication in the homes of the adolescents, in large numbers this has been dragging the adolescent today since his childhood acquired negative behaviors, which are affecting the healthy behavioral and personal development to corroborate and help In a positive way, the proposal was elaborated to give a possible solution to the problem and thus improve the behavior of adolescents and encourage assertive communication.